An Unedited Poem from Ǧabal Nafūsa in the Sormani Library-Milan - Faraj, Ali (Romano-Arabica, 2020)
Italian libraries and museums house a large number of Arab and Islamic manuscripts, but only a few of them have Ibāḍī collections. The central municipal library Biblioteca Sormani, located in Milan, retains a group of Ibāḍī Islam manuscripts, known as Griffini. I have selected, among the others, a poem written by ‘Alī b. al-Ḥāǧǧ Ibrāhīm Muḥammad al-Nalūtī, whose script I have studied, focusing on the vocalization. I have analyzed each verse, deciphering as much as possible and providing a commentary. This poem is composed of thirty-eight verses, mostly about ḥamāsah (war poetry) and madīḥ (praise) and is written in semi-classical Arabic. The introductory verse is composed in al-raǧaz metre: mustafʿilun mustafʿilun mustafʿilun.
Keywords: Littérature -- Djebel Nefousa